2023
DOI: 10.3390/jcm12185937
|View full text |Cite
|
Sign up to set email alerts
|

Remimazolam for Pediatric Procedural Sedation: Results of an Institutional Pilot Program

Tatsuya Hirano,
Yoshitaka Kimoto,
Norifumi Kuratani
et al.

Abstract: Remimazolam, an ultra-short-acting benzodiazepine sedative, was first approved in 2020 in Japan as a general anesthetic for adults. However, its utilization in pediatric settings remains unexplored and, to date, is confined to isolated case reports due to a lack of specific pediatric labeling. The primary objective of our study was to evaluate the safety profile of remimazolam when used for procedural sedation in children following dosages established in adult protocols. Additional parameters, including dosage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…On sedation, it has been reported that remimazolam is less likely to cause bradycardia [ 28 , 29 ]. In a pilot study conducted with children, it was also shown that remimazolam may contribute to reduced bradycardia [ 30 ]. Given these consistent findings, remimazolam may be recommended for patients who are susceptible to bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…On sedation, it has been reported that remimazolam is less likely to cause bradycardia [ 28 , 29 ]. In a pilot study conducted with children, it was also shown that remimazolam may contribute to reduced bradycardia [ 30 ]. Given these consistent findings, remimazolam may be recommended for patients who are susceptible to bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hirano et al 54 found that remimazolam alone may not achieve adequate sedation in some pediatric surgeries. Additionally, anesthesia achieved with multiple agents has been shown to alleviate adverse reactions or enhance the effect of drugs in clinical practice.…”
Section: Rational Dosing Strategies For Remimazolammentioning
confidence: 99%